SKALA WAKTU DAN SUMBER DAYA - Cindy Fatika Sari (PT. Anagata Sembagi Education, 2024)
This article describes the time and resource scales in the implementation of public relations activities. This research uses a qualitative approach method. The purpose of making this article is to find out about the time scale, the form of resources needed by PR and long-term plans in the implementation of activities. The results of this study show that there are two main things that need to be considered, namely effectiveness and efficiency and the need for appropriate techniques.